(untitled) (CHORNOMORSKI BOTANICAL JOURNAL, 2012)
The liverworts flora of the Lapland State Nature Reserve includes 173 species that is 63% of the liverworts biodiversity of the European part of Russia, 66.5% of the North-West of Russia, and 88% of the Murmansk Region. The species diversity of partial liverworts floras of the Lapland State Nature Reserve Mountains varies but slightly: 139 species were found in the Salnye Tundry Mts, 124 species in the Monche-tundra Mts, 133 species in the Chuna-tundra Mts, and 112 species in the Nyavka-tundra. The high diversity observed in the studied sub-regions can be explained by diverse geological, geomorfological and climatic conditions of the area, as well as by intensive research; fairly dense and uniform coverage of liverworts sampling in the area.